Comparison of the adjuvant activity of emulsions with different physicochemical properties on the antibody response towards the venom of West African carpet viper (Echis ocellatus). (1st March 2017) - Valverde, Juan Manuel; Rodríguez, Karina; Herrera, María; Segura, Álvaro; Vargas, Mariángela; Villalta, Mauren; Montero, Mavis; Gutiérrez, Jose María; León, Guillermo
Abstract: Adjuvant emulsions are widely used to enhance the antibody response of the animals used as immunoglobulin source for producing antivenoms. Usually, the adjuvant activity of emulsions is attributed both to their ability to trigger "danger" signals from cells in which they induce death, and to form depots from which immunogens are slowly released. However, there is contradictory evidence suggesting that adjuvant activity of emulsions is independent of the dispersion type and the rate of immunogen release. In order to test how physical properties of emulsions, composed of mineral oil and water, affect their ability to enhance the antibody response towards snake venoms, we compared water-in-oil (W/O) emulsions prepared at volume ratios of 70/30, 50/50 or 30/70, a 50/50 oil-in-water (O/W) emulsion, and a water-in-oil-in-water (W/O/W) multiple emulsion. Comparison included their droplet-size, viscosity, rate of immunogen release and ability to enhance the antibody response of mice immunized with the venom of the African viperid snake Echis ocellatus . It was found that all emulsions released a low amount of venom, and that the 50/50 (W/O) and the multiple emulsion (W/O/W) were those that induced the higher anti-venom antibody response. Our results suggest that the ability of emulsions to enhance the anti-venom response is not associated to their ability to form depots from which the venom is slowly released. Highlights: Emulsions are widely used to enhance the response of the animals used as immunoglobulin source for producing antivenoms. The mechanism by which emulsions exert their adjuvant activity is complex and not completely understood. We compared the adjuvant activity of emulsions with different physicochemical properties. It was found that the 50/50 (W/O) and the multiple emulsion (W/O/W) were those that induced the higher antibody response. Adjuvant activity of emulsions is not associated to their ability to form depots from which the venom is slowly released.